DEVELOPMENT OF A SCIENCE LEARNING MODULE BASED ON THE MENONGKAH KERANG TRADITION TO IMPROVE SCIENTIFIC LITERACY AND SCIENTIFIC ATTITUDES OF JUNIOR HIGH SCHOOL STUDENTS - Ina Lestari; Z. Zulirfan; Evi Suryawati (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2025)
This study aims to develop a science learning module based on the Manongkah Kerang tradition that is valid and practical for use in the learning process. The research method used in this study is Research and Development (RD), referring to the ADDIE model (analysis, design, development, implementation, evaluation). The results of expert evaluations including content, pedagogy, and media experts indicate that the science learning module based on the Menongkah Kerang tradition falls into the very valid category, with an overall average score of 3.78. The student practicality test yielded a score of 3.80, categorized as very practical, while the teacher practicality test scored 3.82, also categorized as very practical. These findings demonstrate that the science learning module based on the Menongkah Kerang tradition is both valid and very practical for classroom use.